Unusual bifid crista galli in a patient with cleft lip and palate - Dedeoglu, Numan; Altun, Oguzhan; Kucuk, Eyup Burak; Altindis, Sedat; Hatunoglu, Erdem (Springer, 2017)
One of the most common craniofacial malformations observed in newborn babies is cleft lip and palate (CLP). This syndrome presents with some anatomic variations. The aim of this study was to understand an anatomic variation of the crista galli that had not been reported previously in patients with CLP. A 17-year-old boy with CLP was referred to an orthodontic clinic for cone-beam computed tomography (CBCT) imaging before treatment. Axial and coronal sections and three-dimensional images showed that the crista galli had bifid heads that were attached to each other. Incomplete ossification had resulted in a bifid crista galli and the appearance of a suture in the anterior coronal section of the CBCT images. This anatomic variation could allow penetration of the anterior fossa during endoscopic surgery, which could be dangerous for the patient.
Keywords: Crista galli; CBCT; Cleft lip and palate